Sound localization in bilateral users of MED-EL COMBI 40/40+ cochlear implants - Nopp, P; Schleich, P; D'Haese, P (Ear and hearing, 2004)
The purpose of the study was to investigate sound localization with bilateral and unilateral cochlear implants. Sound localization tests were performed on 20 bilaterally implanted MED-EL COMBI 40/40+ users. All subjects were bilaterally implanted during adolescence or later. Sound localization was tested in the frontal horizontal plane by using 9 equally spaced loudspeakers and speech-shaped noise bursts at randomized levels. The group of subjects who were bilaterally deafened after 5 to 6 yr of age (18 subjects) showed a statistically significant improvement in sound localization when using both implants, compared with when using only one. The mean deviation between the presentation azimuth and the response azimuth was 16.6 degrees when using both implants, which was on average 37.1 degrees smaller than when using one implant only. When adjusted for the localization error that was constant across loudspeakers, the mean deviation was 15.9 degrees for bilateral implant use, representing an improvement of 30.1 degrees over unilateral implant use. Statistical analysis showed that in this group, performance measures were not correlated with subject details such as age at onset of deafness or duration of unilateral implant use. In contrast, subjects who were bilaterally deafened before 6 yr of age (2 subjects) did not show a benefit in sound localization from bilateral implants. Bilateral cochlear implants offer a substantial benefit in sound localization to late-deafened, late-implanted subjects. The very limited data from early-deafened subjects implanted at a later age could suggest that these subjects may not benefit in sound localization from bilateral cochlear implants. It is possible that early implantation for early deafened subjects might allow better acquisition of spatial hearing, thus leading to improved localization performance.